Asthma and mental health among youth in high-risk service settings. (18th March 2014) - Goodwin, Renee D.; Hottinger, Kate; Pena, Lillian; Chacko, Anil; Feldman, Jonathan; Wamboldt, Marianne Z.; Hoven, Christina
Abstract: Objective : To investigate the prevalence of asthma and mental health problems among representative samples of youth in high-risk service settings and the community, and to examine the relationship between asthma and mental health in these groups. Methods : Data were drawn from the Alternative Service Use Patterns of Youth with Serious Emotional Disturbance Study (SED) ( n = 1181), a combined representative, cross-sectional sample of youth in various clinical settings and the community. Multiple logistic regression analyses were used to examine the association between asthma and mental disorders. Demographic characteristics were investigated as potential confounders. Results : Asthma was common among 15.2% of youth in service settings and 18.8% of youth in the community. The prevalence of mental disorders was extremely high among youth with and without asthma in all service settings, and asthma was associated with increased prevalence of mental disorders among youth in the community, but not among youth in service settings. The relationship between asthma and internalizing disorders among youth in the community does not appear entirely attributable to confounding by demographics. Conclusions : Findings are consistent with and extend previous data by showing that both asthma and mental disorders are disproportionately common among youth in high-risk service settings. Almost half of youth with asthma in service settings meet diagnostic criteria for a mental disorder. Clinicians and policy makers who are responsible for the health care of youth in these high-risk groups should be aware that asthma is common, and that the prevalence of internalizing disorders are especially common among those with asthma.